Social media in B2B: Usage and effects of social media in German B2B companies - Susanne Nördinger; Christoph Desjardins (Journal of Applied Leadership and Management, 2020)
Research questions: How relevant is it for German B2B companies to use social media within marketing? What are the effects of social media usage in German B2B companies and how are they related to specific usage methods of social media? Are there differences in the importance of social media between larger and smaller German B2B companies? Methods: A survey about usage and effects of social media was developed based on the findings of the literature review and distributed to marketing and communication professionals in German B2B companies. On the basis of the answers of 138 participants, 14 hypotheses have been tested with different statistical methods. Results: German B2B organizations attach great importance to social media marketing in general, but do not want to spend more than 20 % of their marketing budget for social media. These companies use social media as brand building and sales support tools, but not for customer relationship management or innovation management. Furthermore, within these 138 German B2B companies, brand advocacy can be enhanced by social media usage as a brand building tool, customer satisfaction as a sales support tool, and customer communication as a customer relationship management tool. Another finding of this study is that smaller and larger German B2B companies attach the same importance on social media.
Keywords: 650